Development of GABARAP family protein-sensitive LIR-based probes for neuronal autophagy - Jeon, Pureum (Mol Brain, 2019)
Autophagy allows for lysosomal cellular degradation of cytosolic components. In particular, neuronal autophagy is essential for cellular homeostasis and neuronal survival and is tightly regulated by several autophagy-related (ATG) proteins in post-mitotic neurons. Among these ATG proteins, the LC3/GABARAP proteins are known to regulate autophagosome biogenesis/maturation and cargo recognition. However, little is known about the role of GABARAP family proteins in neuronal autophagy despite their abundant expression in post-mitotic neurons. We have previously developed HyD (Hydrophobic Domain)-LIR (LC3-interacting region)-based autophagosome markers. In this study, to monitor GABARAP family proteins in autophagosomes of post-mitotic neurons, we improved the sensitivity of the probes for specifically detecting endogenous GABARAP family proteins by adding one more LIR motif to the LIR probes. We have tested the efficiency of two different LIRs, from ULK2 and Stbd1, in regard to their cellular localization to autophagosomes. HyD-2xLIR(ULK2)-GFP and HyD-2xLIR(Stbd1)-GFP demonstrated specific localization to GABARAP-positive autophagosomes relative to LC3B-positive autophagosomes in MEF/HeLa cells in an autophagy-dependent manner. Indeed, HyD-2xLIR(Stbd1)-GFP could efficiently detect GABARAP-positive autophagosomes in cultured cortical neurons. Our improved GABARAP-sensitive probes will contribute toward understanding the specific role of GABARAP family proteins in regard to neuronal autophagy.